Lærdommens billeder : Sæbyværkstedets udsmykninger i fem nordjyske kirker - Lillie, Eva Louise (Kirkehistoriske Samlinger, 1988)
In the first quarter of the 16th century five churches were decorated with wall-paintings by the same workshop in North Jutland: the chancel of Vesterø on Læsø, the porch of St. Budolfi’s in Ålborg, the chancel and nave of the parish church of Vrå, the chancel of the Carmelite church at Sæby, and the south chapel of the Benedictine convent in Dronninglund (formerly Hundslund). The decorations by this workshop differ on several points from other contemporary mural paintings, viz. choice of motifs, their combination and position in the church interior. In Vesterø (ill. 1) the story of the Three Magi is unusual for this period (but not earlier) because it is depicted in the chancel, and the Passion series in Vrå is one of the longest in Denmark (ill.4). The mural in the porch of St. Budolfi’s showing the Miracle of the Palm Tree, bending at the command of the Infant Jesus is exceptional, being the only one of its kind in Denmark (ill.3), and because of its position together with the Sacrifice of Isaac (ill.3). In Sæby Church there is one of the most comprehensive stories of the Childhood of the Virgin, also depicting unusual scenes, for example Joachim taking leave of Anna. Here, the story is juxtaposed with scenes from the Creation (ill.9). In Sæby and Vrå there are motifs (in the chancels) taken from Ars moriendi, the only in existence in Denmark, and at the same time extremely rare in a European context (ill.5-8). At Dronninglund, apart from usual motifs such as, for example, he Annunciation and the Crucifixion, there are also outstanding representations of the Gathering of manna in the desert, the Vision of the emperor, and the Nine heroes (ill. 10-13 and 16). The workshop is noteworthy because it utilises many different models, among which only Biblia Pauperum (ill. 14-15) and Ars moriendi (ill.5-8) shall here be mentioned. The purpose of the wall-paintings in these five churches is not so much to instruct the layman but sooner aimed at the schooled theologian. The intention of the murals is not immediately obvious, and it is necessary to search for their hidden meaning before being able to grasp the ideas behind them. The Vesterø decoration tells the story of the Holy Trinity and the Divinity of Christ, and in St. Budolfi’s, Ålborg, the theme is obedience to God within the framework of the Church. The decoration in Sæby can be interpreted as defending the doctrine of the Immaculate Conception. Christ is the central figure in Dronninglund: Christ as Salvator Mundi, the Lamb of God, the Redeemer of Mankind. The murals have been painted at a time when the doctrines of humanism and Roman Catholic reform began to gain ground, yet they display no sign of influence from these quarters - the oeuvre of this workshop expresses ideas firmly anchored in late medieval piety and theological learning.